OLELT (Online English Language Training) as a means of harnessing human capital and propagating learning organization / Wan Zumusni Wan Mustapha, Norizan Abd Razak and Supyan Hussin - Wan Mustapha, Wan Zumusni; Abd Razak, Norizan; Hussin, Supyan (Research Management Institute (RMI), 2008)
With rapid development in e-learning in Malaysia Higher learning institutions, UiTM also plays a proactive role in knowledge dissemination and acculturation by embarking on online training. With the increasing use of Internet and computer at the workplace, e-training should be recognized as a way to meet the current challenges and workplace demands to propagate life long learning and learning organization. This paper studies the self-directed learning experience on an on-line English Language training program known as Online English Language Training (OLELT). The training program was first implemented on UiTM Kelantan lecturers to help them improve their English Language proficiency. Using a case study, data were collected and analyzed qualitatively using in-depth interviews and observations on ten lecturers from various disciplines. The emerging themes show that online training is efficient, cost effective and motivating if it is properly planned and designed. It also promotes self-paced and continuous learning experience. However, there are barriers and constraints faced by the participants that need to be addressed.